Looking at the Effectiveness of Various Learning Media in Anatomy Education: The Case of a Medical Program in a Public University - Tarawifa, Susan; Enis, Rina Nofri; Shafira, Nyimas Natasha Ayu; Oktari, Intan (Indonesian Research Journal in Education |IRJE|, 2023)
Anatomy education has historically been facilitated by cadavers; therefore, students always need a mentor at all times of study. Along with the dense curriculum, students are required to be able to study independently so various media are needed that can facilitate the student learning process.Â  This study aimed to determine the differences in the level of student knowledge of the anatomical learning materials provided through anatomy atlas, learning videos, and augmented reality (AR) in first-year medical students. This study was quasi-experimental. A total of 100 students became participants in this study that were then divided into 3 groups. Data were collected by giving pre-test and post-test to the student directly. The results of this study showed that the anatomy atlas and augmented reality significantly enhanced studentsâ€™ knowledge in anatomy learning (p=0,004, p=0,000) but there was no significant difference between the three media towards the increasing student scores(p=0,14).